Yearning to Belong : Malaysia's Indian Muslims, Chitties, Portuguese Eurasians, Peranakan Chinese and Baweanese - Pillai, Patrick (Book collections on Project MUSE., 2015)
Malaysia is among the most ethnically diverse and culturally rich nations on earth. Yet much of its cultural wealth lies buried beneath the rubric of its main Malay, Chinese and Indian "race" categories; the dazzling diversity within and outside these groups remains largely unexplored. This book uncovers some of this fascinating diversity through the stories of five little-known acculturated ethnic groups in Peninsula Malaysia. The author, a Malaysian sociologist, delivers an insightful and lucid study of these groups, with some surprising findings. These communities illustrate how much more c.